P230 Ultrasonography-based and Magnetic Resonance-based Lémann Index: two sides of the same coin. (21st January 2022) - Allocca, M; Dell'Avalle, C; Radice, S; Bonifacio, C; Furfaro, F; Zilli, A; D'Amico, F; Peyrin-Biroulet, L; Danese, S; Fiorino, G
Abstract: Background: Lémann Index (LI) is a well-established validated index to assess cumulative bowel damage in Crohn's disease (CD). Magnetic resonance imaging and colonoscopy are usually used to measure LI. We assessed the accuracy of bowel ultrasound in assessing LI and its sensitivity to change in a longitudinal cohort of CD patients, in comparison with magnetic resonance imaging. Methods: We performed a prospective observational study of 60 patients with active CD. All patients underwent bowel ultrasound, magnetic resonance imaging, and colonoscopy at baseline and at reassessment, within 1 year from treatment with biologics (30 patients were treated with adalimumab, 22 with ustekinumab, four patients with infliximab, and four with vedolizumab). The primary analysis was to determine the correlation between magnetic resonance-based LI and ultrasonography-based LI, both at baseline and at reassessment. Additional analyses established the magnitude of change in LI over time, measured by magnetic resonance imaging and colonoscopy, and its correlation with those in LI measured by bowel ultrasound and colonoscopy. Results: The mean values of magnetic resonance-based LI and ultrasonography-based LI at baseline were 6.3 (± 4.8) and 6.4 (± 4.9) respectively, p= 0.39; at reassessment, 5.3 (± 4.6) and 5.5 (± 4.9) respectively, p= 0.30. No differences were observed according to different treatments (Table1 ). There were significant differences between LI assessed at baseline and LI at reassessment, independently by the imaging tool used for measuring it (p < 0.05). Very high correlations were observed between the magnetic resonance-based LI and ultrasonography-based LI (at baseline, r= 0.964, p < 0.0001; at reassessment, r= 0.970, p < 0.0001) (Figure 1 ). The magnitude of change in magnetic resonance-based LI correlated with those in ultrasonography-based LI (r= 0.871; p < 0.0001) (Figure 1 ). Conclusion: LI can be measured by bowel ultrasound alternatively to magnetic resonance imaging, without no meaningful change in its value.